1978
DOI: 10.1159/000148927
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutination and Hemagglutination-inhibition Studies with a Strain of Nebraska Calf Diarrhea Virus (Bovine Rotavirus)

Abstract: A hemagglutinin has been prepared from Nebraska calf diarrhea virus (NCDV) propagated in BS-C-1 cell line. After cesium chloride centrifugation, the hemagglutinin of the bovine rotavirus was found to be associated with intact virions (density 1.355 g/ml) but not with virions lacking an outer capsid layer (density 1.375 g/ml). In hemagglutination-inhibition (HAI) tests, the hemagglutinin reacted specifically with NCDV serum, and HAI seroconversions were detected in some sera tested. Cross-reactions were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…Double-shelled particles of bovine and simian rotavirus strains have been shown to possess a hemagglutinin [Fauvel et al, 1978;Inaba et al, 1977;Kalica et al, 19781. They aggregate erythrocytes from several species including man, monkey, guinea pig, mouse, goose, and chicken.…”
Section: Discussionmentioning
confidence: 99%
“…Double-shelled particles of bovine and simian rotavirus strains have been shown to possess a hemagglutinin [Fauvel et al, 1978;Inaba et al, 1977;Kalica et al, 19781. They aggregate erythrocytes from several species including man, monkey, guinea pig, mouse, goose, and chicken.…”
Section: Discussionmentioning
confidence: 99%
“…However, when neutralizing titres for homologous virus were high, proportionately elevated titres against heterologous virus were obtained (Thouless et al I977a). Recently it has been reported that a haemagglutinin is present in preparations of calf rotavirus (Inaba et al I977;Fauvel et al 1978). Separation of double-and singleshelled virus particles on caesium chloride density gradients demonstrated that doubleshelled particles agglutinated erythrocytes, but single-sheIled particles did not (Fauvel et al I978).…”
Section: Antigenic Relationshipsmentioning
confidence: 99%
“…The hemagglutination titer decreases with trypsin treatment, and, conversely, infectivity increases. In contrast, the hemagglutinating activity of simian and bovine rotaviruses is not affected by trypsin treatment [Fauvel et al, 1978;Inaba et al, 1977;Kalica et al, 19781. Genetic studies of animal rotavirus reassortants, for example, that of simian (RRV) and bovine (UK) rotaviruses which respectively have and do not have hemagglutinin (HA), have revealed that the HA of simian viruses is the fourth gene product, an 82,000 molecular weight (MW) protein [Kalica et al, 19831. Interestingly, monoclonal antibodies directed against the HA of RRV inhibit hemagglutination but also neutralize infectivity [Greenberg et al, 19831.…”
Section: Introductionmentioning
confidence: 99%